Anthropometric and morphological characteristics of elite male cricket bowlers and batters over time: A systematic review - Pote, L.; Nicholls, S.; King, G.; Christie, C. (International Journal of Sports Science & Coaching, 2023)
This research investigated the differences in the anthropometric and morphological characteristics of elite male cricket bowlers and batters over time. A systematic review was conducted according to Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines, between September 2021 and October 2022. A literature search was carried out on three main databases: PubMed, Web of Science, and EBSCOhost. This was based on keywords and several inclusion and exclusion criteria. A quality assessment was carried out using the evaluation criteria for quantitative investigations focusing on the problem statement, design of methods, participant characteristics, outcome measures, sample size, analytical methodology, estimation of variance, reporting of results, and overall conclusions, to assess manuscript quality. Data were presented as mean ± SD where appropriate. Fifty-two papers matched all criteria and specific data from each was used for the systematic review. The most common measures investigated were stature, mass, and percentage of body fat. Elite bowlers were found to be significantly (p < 0.001; ES = 1.29) heavier (83.54 ± 4.42 kg vs 79.02 ± 4.26 kg) and significantly taller (p < 0.01; ES = 1.03) (185.64 ± 3.48 cm vs 181.23 ± 2.57 cm) than batters. A strong, positive and significant (p < 0.05) correlation (R2 = 0.77) was shown for batters between stature and time (years) (1987: 179.80 cm; 2021: 183.00 cm). Research on the anthropometrical and morphological characteristics comparing elite cricket bowlers and batters over time is limited. Further inquiry is needed to quantify the effect of these different traits on batting and bowling performance. This is important for player selection, talent identification, and program design.